Particulate colloids - Lyklema, J. (Fundamentals of interface and colloid science, 2005)
Volume IV (2005) covers preparation, characterization of colloids, stability and interaction between pairs of particles, and in concentrated systems, their rheology and dynamics. This volume contains two chapters written, or co-authored by J. Lyklema and edited contributions by A.P. Philipse, H.P. van Leeuwen, M. Minor, A. Vrij, R. Tuinier and T. van Vliet. The volume is logically followed by Vol V, but is equally valuable as a stand alone reference. * Combined with part V, this volume completes the prestigious series Fundamentals of Interface and Colloid Science * Together with volume V this book provides a general physical chemical background to colloid science * Covers all aspects of particle colloids.